Analysis of Radiotherapy and chemotherapy induced toxicity on rodents (Swiss albino) and pharmacological importance of Pistia stratiotes - S. Patil; N. Dhele; S. Pawar; N. Ganesh (International Journal of Phytomedicine, 2012)
Herbal medicines has been reported to play an important role i n the discovery of new drugs for t he treatment of human diseases, including cancer [1]. Many herbal remedies have shown to play anticancer role through multiple mechanisms. Our present work i s an at t em pt t o screen s om e essential components from the water weed Pistia stratiotes and to study its potentiality against the side effects induced by radiotherapy and chemotherapy